Review and publication of protocol submissions to Trials – what have we learned in 10 years? - Li, Tianjing; Boutron, Isabelle; Salman, Rustam A; Cobo, Erik; Flemyng, Ella; Grimshaw, Jeremy M; Altman, Douglas G (Université d'Ottawa | University of Ottawa, 2016)
Abstract Trials has 10 years of experience in providing open access publication of protocols for randomised controlled trials. In this editorial, the senior editors and editors-in-chief of Trials discuss editorial issues regarding managing trial protocol submissions, including the content and format of the protocol, timing of submission, approaches to tracking protocol amendments, and the purpose of peer reviewing a protocol submission. With the clarification and guidance provided, we hope we can make the process of publishing trial protocols more efficient and useful to trial investigators and readers.